The Effects of Repeated Lineups and Delay on Eyewitness Identification - Lin, Wenbo (2017)
Prior eyewitness research has examined the effects of repeated identification procedures and delays on eyewitness identification, but these studies have either confounded these two factors or studied them in isolation. Experiment 1 attempted to disentangle these factors through systematic manipulations of the number of repeated lineups and the length of delay between the original event and the first lineup. Experiment 2 examined whether the length of delay between two lineups (Lineups 1 and 2) affects the subsequent lineup identification decisions. We found that people were more inclined to choose when a lineup was repeated. A longer delay between the crime and the initial identification decreased the tendency to choose for target-present lineups but not for target-absent lineups. Regardless of delay conditions, both correct and incorrect decisions in Lineup 1 were often repeated in Lineup 2. Compared to response times, confidence was a more reliable indicator of identification accuracy. More importantly, in both experiments, the confidence-accuracy relationship remained intact despite the effects of repeated lineups and delay